Intravesical Bacillus Calmette-Guérin versus mitomycin C for Ta and T1 bladder cancer: abridged summary of the Cochrane review - Hahne, Stefanie; Kunath, Frank; Coles, Bernadette; Dräger, Désirée Louisê; Krabbe, Laura-Maria; Dersch, Rick; Kilian, Samuel; Jensen, Katrin; Dahm, Philipp; Meerpohl, Jörg J. (Investigative and clinical urology, 2020)
People with urothelial carcinoma of the bladder are at risk for recurrence and progression following transurethral resection of a bladder tumour. Mitomycin C (MMC) and Bacillus Calmette-Guérin (BCG) are commonly used, competing forms of intravesical therapy for intermediate- or high-risk non-muscle invasive (Ta and T1) urothelial bladder cancer but their relative merits are somewhat uncertain. Although several systematic reviews and meta-analyses have been conducted on this topic, it still remains unclear what the optimal treatment dose and schedule might be, as well as the question of which people benefit most from one or the other agent.
Gesehen am 29.10.2020